2005
DOI: 10.1093/eurheartj/ehi473
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blocker treatment of chronic systolic heart failure improves prognosis even in patients meeting one or more exclusion criteria of the MERIT-HF study

Abstract: In clinical practice only the smaller part of the population to be treated for chronic systolic heart failure meets the inclusion criteria of the MERIT-HF study. However, beta-blocker treatment is associated with a significantly reduced long-term mortality even in patients meeting one or more exclusion criteria of the MERIT-HF study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
0
8
0
7
Order By: Relevance
“…However, over the past two decades there has been a substantial reduction in mortality, probably due to more widespread use of renin-angiotensin aldosteron (RAAS) and beta-receptor blocking agents [2,4,5]. Studies from Sweden and from Scotland have shown that the prognosis has improved [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, over the past two decades there has been a substantial reduction in mortality, probably due to more widespread use of renin-angiotensin aldosteron (RAAS) and beta-receptor blocking agents [2,4,5]. Studies from Sweden and from Scotland have shown that the prognosis has improved [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Auch Patienten, die aufgrund von Ausschlusskriterien nicht in kontrollierte Studien eingeschlossen wurden, sollte eine leitlinienkonforme Therapie nicht grundsätzlich vorenthalten werden [19].…”
Section: Herzinsuffizienz: Probleme Bei Der Medikamentösen Einstellungunclassified
“…Die 1-Jahres-Sterblichkeit der Patienten mit chronischer Herzinsuffizienz reicht von ca. 10% bis 50%, abhängig vom Schweregrad der Erkrankung und abhängig von der Umsetzung leitliniengerechter therapeutischer Maßnahmen [12][13][14][15]. Die Herzinsuffizienz war in Deutschland im Jahre 2004 bei Männern die vierthäufigste Todesursache nach KHK, akutem Myokardinfarkt und bösartigen Neubildungen der Bronchien und der Lunge (15 053 Todesfälle).…”
Section: Kardiovaskuläre Erkrankungen In Deutschlandunclassified
“…Durch die medikamentöse Therapie mit ACEHemmern und/oder AT1-Blockern, Beta-Blockern, Diuretika und Aldosteron-Antagonisten wird nicht nur die Leistungsfähigkeit dieser Patienten, sondern auch deren Lebenserwartung signifikant verbessert [12,13,15].…”
Section: Chronische Herzinsuffizienz Evidenzunclassified